2021
DOI: 10.1016/j.jhep.2021.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury in COVID-19 and IL-6 trans-signaling-induced endotheliopathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 44 publications
2
102
0
1
Order By: Relevance
“…13,21 Another potential cause of liver injury is a hypercoagulable state, which also has been associated with COVID-19. Studies have shown increased markers for endothelial cell and platelet activation in patients with severe disease, potentially resulting in microthrombi [22][23][24] that could affect liver blood flow. We initially defined the hypercoagulable state as increased D-dimer and fibrinogen levels, however, because these tests also correlated significantly, we defined it solely as a D-dimer level of 5 mg/L or higher throughout hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…13,21 Another potential cause of liver injury is a hypercoagulable state, which also has been associated with COVID-19. Studies have shown increased markers for endothelial cell and platelet activation in patients with severe disease, potentially resulting in microthrombi [22][23][24] that could affect liver blood flow. We initially defined the hypercoagulable state as increased D-dimer and fibrinogen levels, however, because these tests also correlated significantly, we defined it solely as a D-dimer level of 5 mg/L or higher throughout hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulopathy and liver endotheliopathy have been suggested to be at least partially driven by interleukin (IL)-6 trans-signaling, which would lead to the expression of procoagulant (such as factor VIII or von Willebrand factor) and proinflammatory factors as well as increased platelet attachment in liver sinusoidal endothelial cells. Interestingly, these effects were blocked by soluble gp130, which acts as an IL-6 trans-signaling inhibitor, and the janus kinase inhibitor ruxolitinib, providing support for these therapeutic approaches[ 22 ]. Histopathologic features suggestive of some level of cytopathic injury, however, have been also observed in liver biopsies[ 23 ].…”
Section: Covid-19 and The Livermentioning
confidence: 99%
“…It is noteworthy that COVID-19 thrombosis and severe illness are more frequent in patients with metabolic syndrome and non-alcoholic fatty liver disease (NAFLD). 7,8 In the cohort of patients from the study by McConnell, Kawaguichi et al, 14 there was a high prevalence of steatosis, and it is also possible that, in the context of systemic inflammation, liver steatosis rather than endotheliopathy, or the combination of the 2 elements, may favor liver neutrophil infiltration. Furthermore, IL-6 is only one of several cytokines which participate in the pathogenesis of COVID-19, 20 and the role of other cytokines or liver cells (e.g.…”
mentioning
confidence: 99%
“…12 Interleukin (IL)-6 has been postulated as a key proinflammatory cytokine in COVID-19 pathogenesis and IL-6 inhibition may improve outcomes and survival of patients with severe disease. 13 In this issue of Journal of Hepatology, McConnell, Kawaguchi et al 14 investigated the role of IL-6 signaling in the induction of a pro-coagulatory and proinflammatory phenotype in liver sinusoidal endothelial cells (LSECs), also called endotheliopathy by some authors. 15 IL-6 is a cytokine produced by macrophages, endothelial cells, T cells and fibroblasts upon stimulation of Toll-like receptor 4, IL-1 or tumor necrosis factor-a.…”
mentioning
confidence: 99%
See 1 more Smart Citation